Perceptions of opportunity recognition behaviour in the South African financial sector - Wood, Eric Anthony (My University, 2012)
The world is in the midst of a new wave of economic development with entrepreneurship and innovation as the catalysts. The ability to continually innovate and to engage in an ongoing process of entrepreneurial action has become the source of competitive advantage and a lack of entrepreneurial actions in today’s global economy could be a recipe for failure (Kuratko, 2009). Organisations need to keep abreast of developments in their business environment and continually identify and evaluate opportunities if they are to prosper in a rapidly changing world, and they must become more entrepreneurial as their corporate environments become more dynamic and increasingly competitive (Shepherd, Patzelt and Haynie, 2009). Opportunity recognition remains an important issue for academic research. This research report aims at making a modest contribution to further understand opportunity recognition behaviour of employees within their existing work environment. The research focussed on employees working in the South African financial sector, and examined their perceptions of opportunity recognition behaviours and motivators. An understanding of these important behaviours and motivators will allow senior management of corporate entities to have a better understanding of the opportunity recognition processes by employees, and to put in place mechanisms that facilitate and support these processes in search of robust entrepreneurial activities. Apart from the economic rationale, the motivations for studying employees’ behaviour come mainly from the limited number of studies of this nature that have been carried out in emerging economies. The study is performed using data from 195 employees drawn from 23 financial sector companies in South Africa. This research concludes that South African financial sector employees perceive themselves as showing strong levels of opportunity recognition behaviours, and opportunity recognition motivators are also perceived important in promoting entrepreneurial initiatives. The empirical study reveals that there is a significant positive relationship between opportunity recognition behaviours and the frequency of opportunities recognised. vi Success is found to have a moderating effect on the relationship between frequency of opportunity recognition and perceptions of opportunity recognition behaviours. Respondents, who have a low or medium number of successfully implemented opportunities, recognise a higher number of opportunities as their opportunity recognition behaviour increases. However, those respondents with a high number of successfully implemented opportunities tend to show a slight decrease in the total number of opportunities identified as their opportunity recognition behaviour increases. A cluster analysis was carried out to provide a deeper understanding of opportunity recognition behaviours and motivators, and three distinct clusters with differing characteristics were identified. These clusters are named according to the characteristics displayed by the respective clusters (corporate achievers, mavericks, and doers). The corporate achievers cluster tends to perceive high levels of opportunity recognition behaviours and motivators. This high proportion of perceived alignment to company strategy combined with high levels of opportunity recognition behaviours may encourage more of the proposed opportunities to be in line with company strategy, which in turn may lead to the higher proportion of successfully implemented opportunities. The mavericks cluster recognise a large number of opportunities, but are behind the corporate achiever cluster when it comes to the proportion of successfully implemented opportunities and perceive low alignment to company strategy. Although this cluster shows a large proportion of opportunities proposed for their current company, their low perception of alignment to company strategy may mean that the opportunities they recommend do not always fit into the company strategy, which may explain their lower proportion of successfully implemented opportunities. The doers cluster tends to perceive low levels of opportunity recognition behaviour and motivators, as well as low levels of alignment to company strategy. Respondents in this cluster seem to do their work, but show low levels of entrepreneurial orientation.
Keywords: New venture creation; Entrepreneurship; Innovation; Financial sector